EVALUASI KEMAMPUAN FISIK ATLET PB PASHA JAYA TAHUN 2024 - Masri, Masri; Musran, Musran; Mansur, Mansur; Karimuddin, Karimuddin; Ammar, Zahran (Jurnal Dedikasi Pendidikan, 2025)
Evaluation of athletes' physical condition is carried out at PB Pasya Jaya to assess the development of their abilities whether they are up to standard. This research aims to evaluate the physical abilities of PB Pasha Jaya athletes in 2024. The method used is a quantitative descriptive approach. The population of the study consists of PB Pasha Jaya athletes, and the sample was obtained using total sampling technique, involving 14 PB Pasha Jaya athletes as the sample. Data collection was conducted through physical tests, which included: 1) arm muscle power test, 2) leg muscle power test, 3) flexibility test, 4) agility test, and 5) cardiorespiratory endurance test. Data analysis was performed using percentage frequency distribution. The evaluation results show that:1) Arm muscle power has an average of 390.36 (42.86%) in the moderate category, 2) Leg muscle power with an average of 37.79 (92.86%) is in the very poor category, 3) Flexibility with an average of 14.9 (50.00%) falls into the good category, 4) Agility with an average of 12.75 (64.29%) is also in the good category, and 5) Cardio- respiratory endurance with an average of 2.45 (42.86%) is in the moderate category. The conclusion of the study is that flexibility and agility are superior to muscle power and heart-lung endurance, so training is needed to improve these two aspects in order to achieve physical balance